Continuous papaveretum infusion for the control of pain in painful sickling crisis. - Sartori, P C (1990)
We describe our experience of using continuous papaveretum infusions to control pain in 24 children admitted on 45 occasions with painful sickling crisis. The children were aged from 1.7 to 14.3 years. Infusion duration ranged from one to nine days (median three days), total dose from 0.3 to 21 mg/kg (median 2.4 mg/kg), with a pronounced tendency for dosage to increase with increasing age. No respiratory depression was observed. One infusion was discontinued because of cerebral toxicity.